Patients with non-ST segment elevation acute coronary syndromes managed without coronary revascularization: A population needing treatment improvement. (15th October 2017) - Menozzi, Alberto; De Servi, Stefano; Rossini, Roberta; Ferlini, Marco; Lina, Daniela; Abrignani, Maurizio Giuseppe; Capranzano, Piera; Carrabba, Nazario; Galvani, Marcello; Marchese, Alfredo; Mazzotta, Gianfranco; Moretti, Luciano; et al.
Abstract: NSTE-ACS patients are a heterogeneous population, with different clinical features and prognosis. A large proportion of them is medically managed, without any revascularization. In the EYSHOT and FAST-MI registries such patients were 40% and 35%, respectively. These patients are at higher risk of adverse cardiovascular events and have a worse prognosis compared with those receiving revascularization. Medically managed NSTE-ACS patients consist of different subgroups: those not undergoing coronary angiography, those without significant coronary artery disease, and those with coronary stenoses not referred to revascularization. Patients with NSTE-ACS for whom a conservative strategy without coronary angiogram is planned must be very carefully selected. In patients with comorbidities, frailty, or advanced age, a careful balance between benefits and risks is needed to choice the management strategy (perform or not coronary angiography and/or revascularization), as evidence-based medicine data are lacking in the setting of frailty and comorbidities. In this decisional process, it should be also taken into consideration the role of coronary anatomy in risk stratification and treatment guidance. NSTE-ACS patients managed without revascularization less frequently receive guideline-recommended pharmacological treatment. Dual antiplatelet therapy (DAPT) is recommended for 12 months also in medically managed patients, after careful balancing of ischemic and bleeding risk. In these patients it is mandatory to optimize pharmacological treatment, including antiplatelet therapy, to improve outcome. In NSTE-ACS medically managed, the proportion of patients discharged with DAPT should be increased in comparison with current practice, and the use of ticagrelor in place of clopidogrel should be considered in selected patients.